The Effect of Jeopardy Game on Vocabulary Mastery in Eleventh Grade at SMAN1 Kamang Magek - Tasya Lavinska Agustin; Yetti Zainil (Journal of English Language Teaching, 2022)
A quasi-experimental research was employed in this research. The objective of this research was aimed to determine the effect of the Jeopardy game on vocabulary mastery in eleventh grade at SMAN1 Kamang Magek. The SMAN1 Kamang Magek students in the eleventh-grade comprised the research's sample. The experimental class comprised of 23 students from XI MIPA 1. However, the control class comprised of 25 students from XI IPS 2. The pre-test and post-test parts of the vocabulary test that was obtained in this research were separated. 30 multiple-choice questions were used to build the instruments. According to data analysis using the Paired Sample T-Test, the experimental class's mean pre-test score was 19.96, while its mean post-test score was 60.26. It was undeniable that Jeopardy is used to instruct students perform better than those who are taught using non-Jeopardy. The research's null hypothesis (H0) is rejected since the data show that the 2-tailed significance value is less than 0.05 (0.05). The first hypothesis (Ha) is therefore accepted, and it is asserted that the Jeopardy game is effective in terms of vocabulary mastery.